Hydrodynamically guided hierarchical self-assembly of peptide-protein bioinks - Hedegaard, Clara L. (2019)
Effective integration of molecular self‐assembly and additive manufacturing would provide a technological leap in bioprinting. This article reports on a biofabrication system based on the hydrodynamically guided co‐assembly of peptide amphiphiles (PAs) with naturally occurring biomolecules and proteins to generate hierarchical constructs with tuneable molecular composition and structural control. The system takes advantage of droplet‐on‐demand inkjet printing to exploit interfacial fluid forces and guide molecular self‐assembly into aligned or disordered nanofibers, hydrogel structures of different geometries and sizes, surface topographies, and higher‐ordered constructs bound by molecular diffusion. PAs are designed to co‐assemble during printing in cell diluent conditions with a range of extracellular matrix (ECM) proteins and biomolecules including fibronectin, collagen, keratin, elastin‐like proteins, and hyaluronic acid. Using combinations of these molecules, NIH‐3T3 and adipose derived stem cells are bioprinted within complex structures while exhibiting high cell viability (>88%). By integrating self‐assembly with 3D‐bioprinting, the study introduces a novel biofabrication platform capable of encapsulating and spatially distributing multiple cell types within tuneable pericellular environments. In this way, the work demonstrates the potential of the approach to generate complex bioactive scaffolds for applications such as tissue engineering, in vitro models, and drug screening.